Special Issue on Assistive and Rehabilitation Robotics - Mohammed, Samer; Park, Hae Won; Park, Chung Hyuk; Amirat, Yacine; Argall, Brenna (Autonomous robots, 2017)
Assistive and rehabilitation robotics currently covers a broad spectrum of research areas, from intelligent robots that act as aides, companions and educators; to robots that provide physical assistance for mobility, manipulation and support; to embedded robotics, ambient intelligence and intelligent spaces. People whose ability to perform daily living activities is limited or inhibited by injury, disease or impairment include (but are not limited to) stroke survivors with sustained neurological injuries, elderly populations with skeletal muscle weakness, persons with low-vision or blindness, traumatic injuries to the brain or spinal cord, and a variety of degenerative diseases that affect cognition, muscle tone and motor control.Over the last decade, robotics technologies increasingly interact closely with the humans they are assisting. Improvements in sensor technologies, hardware design and control have enabled this. Augmenting assistive machines with robotics intelligence in particular has made great strides—including intelligence found in wearable robots, prostheses, intelligent walkers and canes, and autonomy found in wheelchairs and robotic arms. Moreover, the emergence of novel adapted technologies, such as those in wearable sensors and soft robots, are gaining in popularity—and not the least because of considerable reductions in cost, size and energy consumption. There also has been a considerable push for assistive robots that serve as cognitive and educational aides, and provide coaching to improve health outcomes. Importantly, subject studies with such robots performed in-situ—in the human’s environment rather than the laboratory—have been gaining momentum.This Special Issue on Assistive and Rehabilitation Robotics grew out of the joint efforts of three distinct workshops that were organized in conjunction with the 2014 IEEE/RSJ International Conference on Robotics and Intelligent Systems (IROS), held in Chicago, Illinois USA, from September 14th to 18th, 2014. These workshops were entitled: “Assistance and Service Robotics in a Human Environment”,1 “Rehabilitation and Assistive Robotics: Bridging the Gap Between Clinicians and Roboticists”,2 and “Assistive Robots for Individuals with Disabilities: HRI Issues and Beyond”.3The three workshops gathered leading researchers in the field of assistive and rehabilitation robotics. Fruitful discussion among the speakers and the attendees centered around the state of the art and the challenges and limiting factors for developing sustainable robotics solutions for human assistance and rehabilitation.Following the three workshops, we guest editors launched this Special Issue through a call for papers that included the participants of the three workshops and also the larger research community. Following the open call, we collected 98 extended abstracts on topics ranging from human-robot interaction and social interaction, to healthcare and well-being, to intelligent habitats and mobility assistance. After a careful review process, 22 abstracts were invited to submit full papers. Of these, 14 papers were accepted for publication in the Special Issue.The papers of the Special Issue cover a broad range of topics, from robots that assist with manipulation and mobility (Sect. 3.1), to those that aid in education, cognitive and physical rehabilitation using social interaction capabilities (Sect. 3.2), to those that physically augment the human body (Sect. 3.3).